Elevated neopterin and decreased IL-4, BDNF levels and depression in lymphoma patients receiving R-CHOP chemotherapy - Mishra, Pinki; Bhurani, Dinesh; Nidhi, (Frontiers in Neurology, 2024)
Objective Depression is the most commonly observed psychological manifestation experienced by individuals diagnosed with cancer. The purpose of the study was to investigate the association between levels of IL-4, BDNF, neopterin, and depressive symptoms in lymphoma patients receiving consecutive cycles of chemotherapy. Methods Newly diagnosed lymphoma patients scheduled to receive R-CHOP chemotherapy were enrolled. Effects of R-CHOP on circulatory biomarkers and depressive symptoms were assessed at three-time points [baseline assessment 7 days before the first dose of chemotherapy (TP1), interim assessment after the third cycle of chemotherapy (TP2), and follow-up assessment after the 6th cycle of chemotherapy (TP3)]. Results Seventy lymphoma patients, with a mean age of 44.17 ± 13.67 years, were enrolled. Patients receiving R-CHOP were found significantly increased neopterin levels between given time points TP1 vs. TP2, TP1 vs. TP3, and TP2 vs. TP3 (p < 0.001). However, IL-4 and BDNF levels significantly decreased with consecutive cycles of chemotherapy (p < 0.001). On Patient Health Questionnaire assessment (PHQ-9), scores of items like loss of interest, feeling depressed, sleep problems, loss of energy, and appetite problems were found significantly affected with consecutive cycles of chemotherapy (p < 0.001). The study found weak negative correlations between IL-4, BDNF, and neopterin levels and changes in PHQ-9 scores at both TP2 and TP3, suggesting a potential inverse relationship between these markers and depression symptoms. Conclusion In conclusion, the present study suggests a potential link between elevated neopterin levels, decreased IL-4, and BDNF levels, and the presence of depression in lymphoma patients receiving R-CHOP chemotherapy. This study provides valuable insights into understanding the emotional challenges faced by cancer patients, offering information for more personalized interventions and comprehensive support approaches within the oncology setting.